"Journalism ideology" and its influence on the producers of Radio Sonder Grense radio current affairs. Issue 2 (3rd April 2017) - Jansen van Vuuren, Anna-Marie
ABSTRACT: In the same way that people can have a political or a personal ideology, their professional identities and how they practise a craft or an occupation may be influenced by what can be labelled as a "professional ideology". Through conducting interviews with the producers of the South African Broadcasting Corporation (SABC) Afrikaans radio programmes Monitor, Spektrum and Naweek-Aktueel, this article reports on research which showed that there is indeed such a thing as a "journalism ideology". The interviews focused on how "internal influences" – such as a journalist's background and training, newsroom routines – and "external influences" – such as the audience – influenced the decisions they made in choosing news stories and producing content. This "journalism ideology" influences the producers and in turn the news content of these current affairs programmes that are listened to daily by almost two million listeners. The conclusion drawn from the study is that, although the participants' "journalism ideology" largely determines the news stories for their programmes, structural forces, newsroom routines and organisational constraints often dictate their actions. Finally, although all the participants saw themselves as "watchdogs of democracy", internal pressures within the SABC could endanger that role.